2021
DOI: 10.3389/fvets.2021.687922
|View full text |Cite|
|
Sign up to set email alerts
|

L-Ascorbic Acid Shapes Bovine Pasteurella multocida Serogroup A Infection

Abstract: Bovine Pasteurella multocida serogroup A (bovine PmA) is one of the most important pathogens causing fatal pneumonia in cattle. However, it is largely unknown how nutrition shapes bovine PmA infection. Here, we discovered that the infected lung held the highest bacterial density than other tissues during infection. By screening the different metabolites between high (lung)- and low (liver)-bacterial density tissues, the present work revealed that L-ascorbic acid and L-aspartic acid directly influenced bovine P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…In our previous work [ 21 ], we found that mice intranasally infected with PmCQ2 exhibited severe lung damage and extrapulmonary infections. Here, we repeated previous work and found that intranasal infection with 1 × 10 4 CFU of lethal PmCQ2 indeed induced serious lung damage in mice in a time-dependent manner (Figures 1 A through C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [ 21 ], we found that mice intranasally infected with PmCQ2 exhibited severe lung damage and extrapulmonary infections. Here, we repeated previous work and found that intranasal infection with 1 × 10 4 CFU of lethal PmCQ2 indeed induced serious lung damage in mice in a time-dependent manner (Figures 1 A through C ).…”
Section: Resultsmentioning
confidence: 99%
“…As a respiratory pathogen, P. multocida infection, particularly capsular type A infection, frequently causes clinically detectable pulmonary damage [ 18 ]. Nevertheless, there is a growing body of evidence indicating that P. multocida , including capsular type A, can both damage the host's respiratory system and leak into its blood circulation system (bacteremia), leading to extrapulmonary infections [ 19 21 ]. Notably, P. multocida bacteremia and P. multocida -induced extrapulmonary damage have become increasingly common in the clinic, suggesting that P. multocida -induced systemic infection could be an important part of its pathogenesis [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pm can be classified into 5 serotypes, based on their capsule characteristics: A, B, D, E and F [5]. Among these, Pm serogroup A (PmA), which is usually found in domestic animals, especially in cattle, rabbits and chickens, is known to cause fatal pneumonia, resulting in significant economic losses in animal husbandry worldwide [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium was named after Louis Pasteur, who first recognized P. multocida as the causative agent of fowl disease in 1880 [1]. P. multocida is a widespread pathogen capable of infecting a wide variety of animals [2][3][4] and an opportunistic pathogen of humans. It is the primary causative agent of fowl cholera in chickens [5], hemorrhagic septicemia in ungulates, snuffles in rabbits [6], and progressive atrophic rhinitis or pneumonia in pigs [7].…”
Section: Introductionmentioning
confidence: 99%